Technological Pedagogical Content Knowledge (TPACK) : An Investigation with Informatics Engineering Students - Imansari, Nurulita; Prastyaningrum, Ihtiari; Kholifah, Umi (International Journal for Educational and Vocational Studies)
The purpose of this study was to determine the readiness of TPACK from informatics engineering education students who are vocational teachers candidates in Indonesia. A teacher candidates must be equipped with TPACK, which is a synergy between mastering content, pedagogy, and technology in learning to answer the challenges of teaching in the 21st-century. TPACK readiness data for the vocational teacher candidates was measured using a TPACK assessment questionnaire containing elements of CK, PK, TK, PCK, TCK, TPK, and TPACK. The subjects of this study amounted to 39 students. This study was conducted in Learning Planning course.  The findings of this study indicated that TPACK readiness was a good category but still needs to be improved for the pedagogical readiness.